The Development of pre-examination and triage management in dental clinics under public health events from the perspective of COVID-19 epidemic (从新型冠状病毒肺炎疫情看公共卫生事件下口腔门诊预检分诊管理发展) - SHE Lin (沈琳); CHU Xiaoyu (楚小玉); GAO Yu (高宇) (中西医结合护理)
The WHO has declared the outbreak of COVID-19 a public health emergency of international concern. Oral pre-examination and triage work is one of the central tasks of epidemic prevention and control in dental medical institutions. This article introduces the development of pre-examination and triage management in the Outpatient Department of Peking University School and Hospital of Stomatology in epidemic prevention and control. Based on the experience in diagnosis and management, gradually explore the management of pre-examination and triage that conforms to the characteristics of the dental profession. By clarifying the organization and management of pre-examination and triage work in outpatient clinics, establish pre-examination and triage work systems, job responsibilities, and formulate pre-examination of dental outpatients according to patient risk classification. The primary screening process and the tertiary screening plan, various emergency plans and the treatment process for special patients, strengthen the pre-inspection staff's study of prevention and control policies and regulations, and gradually form the dental clinic pre-examination score Diagnosis management system. At the same time, it is also seen that in the normalization of epidemic prevention and control for several years, the development of oral pre-examination and triage has become more standardized and more information technology has been used to help fight the epidemic. (新型冠状病毒肺炎疫情为“国际关注的突发公共卫生事件”。口腔预检分诊工作是口腔医疗机构疫情防控的中心工作之一, 本文介绍了疫情防控中北京大学口腔医院门诊部预检分诊管理的发展。在借鉴国内外综合医院预检分诊管理经验基础上, 逐渐摸索符合口腔专业特性的预检分诊管理, 通过明确门诊预检分诊工作组织管理, 建立预检分诊工作制度、岗位职责、根据患者风险分类制定口腔门诊患者预检初级筛查流程和三级筛查方案、各类应急预案及特殊患者的处置流程, 加强预检工作人员对防控政策法规学习、院感防控知识培训考核演练等逐步形成口腔门诊预检分诊管理体系。同时, 常态化疫情防控工作中, 口腔预检分诊的发展更加规范化, 更多地运用信息技术助力疫情防控。)